1975
DOI: 10.1177/002383097501800407
|View full text |Cite
|
Sign up to set email alerts
|

Context and Complexity in Working Class Language

Abstract: The research consisted of a comparative analysis of the written language of a working-class group of subjects and a middle-class group, the aim being to test Bernstein's socio-linguistic theory of a class-based limitation to a restricted ' code. Both groups of subjects were given essay titles demanding different forms of stylistic treatment. The written language they produced was then analysed to assess and compare the degree of stylistic variation it contained. On certain linguistic items stylistic 'shifts ' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…These were examples of internalized oppression (Rosenblum & Travis, 2008). Privilege marginalized the voices of non-dominant communicators within American culture (Rushton & Young, 1975) and created communicative barriers for working-class, minority job seekers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were examples of internalized oppression (Rosenblum & Travis, 2008). Privilege marginalized the voices of non-dominant communicators within American culture (Rushton & Young, 1975) and created communicative barriers for working-class, minority job seekers.…”
Section: Resultsmentioning
confidence: 99%
“…Communicative differences and discrimination have emerged at the intersection of race and social class and carried important implications for job search training and reemployment. Differences in amounts of verbosity (Dougherty, 2011), identity negotiation (Callahan, 2008), language use (Macaulay, 2002; Rushton & Young, 1975), politeness norms (Mills, 2004), silence (Clair, 1998; Covarrubias, 2007), volume (Morris, 2007), emotion (Lareau, 2003), (non)familial social interaction partners (Lareau, 2003), speech style stereotypes (Popp, Donovan, Crawford, Marsh, & Peele, 2003), value of talking (Philipsen, 1975), and computer literacy were elements that contributed to and reflected differing communication behaviors and expectations across social class and racial lines. Popp and colleagues (2003) examined White individuals’ perceptions of Black communicators, who were consistently judged to be more emotional, more playful, and less appropriate than White speakers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand Rushton and Young (1975), in a study of writing by lower and middle class adolescents, showed that there was stylistic variation in the writing of both groups; furthermore, the stylistic variation was greater for the lower class subjects. Lower class subjects were found to use a more clearly defined technical style than their middle class counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…Although these communication norms are not inherently bad or wrong, they are often socially compared to white-collar communication norms where verbose language use is typical (Macaulay, 2002;Stuber, 2006), communicatively highlighting and summarizing ideas are common (Schatzman & Strauss, 1955), emotional displays are controlled (Kramer & Hess, 2002;Lubrano, 2004), and conversational partners often include weak ties (Lareau, 2011). Scholars maintain that blue-collar communication norms are viewed through a deficit model and thus stigmatized in social life across the life span (Dougherty, 2011;Mills, 2004;Rushton & Young, 1975).…”
Section: Social Class and Communication Biasmentioning
confidence: 99%